2020
DOI: 10.1111/jmg.12527
|View full text |Cite
|
Sign up to set email alerts
|

High‐P granulites of the Songshugou area (Qinling Orogen, east‐central China): Petrography, phase relations, and U/Pb zircon geochronology

Abstract: High-pressure (HP) granulites provide telling records of mineral reactions at upper mantle to lower crustal levels and key information on the fate of material in subduction systems. The latter especially applies when they abut eclogite and mantle dunite because such rock associations are crucial for understanding the incompletely known processes at the interface of converging plates. A continental arc, active c. 520-395 Ma ago, formed an enigmatic example of such a rock association in the Songshugou area, Qinl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 113 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…In addition, it could also be possible that the estimated peak metamorphic conditions of exhumated metamorphic rocks are deviated from the true values. On the one hand, as high/ultrahigh pressure (HP/UHP) rocks usually underwent significant heat overprinting during the exhumation stage, especially for continental subduction zones such as those in the North Dabie UHP belts, China (e.g., Gao et al., 2017), the North Qinling orogen, China (e.g., Bader et al., 2020), and the Western Gneiss Region, Norway (e.g., Butler et al., 2018), it is reasonable to assume that the re‐equilibration of mineral compositions in the exhumation stage could lead to the calculated temperature ( T ) at P max to a higher value. In comparison to modeling results, temperatures recorded by exhumed oceanic rocks show smaller discrepancies than continental rocks (Agard et al., 2018; Penniston‐Dorland et al., 2015), supporting that part of the recovered peak P – T conditions of exhumed continental rocks with high temperatures may be influenced by decompressional heating.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it could also be possible that the estimated peak metamorphic conditions of exhumated metamorphic rocks are deviated from the true values. On the one hand, as high/ultrahigh pressure (HP/UHP) rocks usually underwent significant heat overprinting during the exhumation stage, especially for continental subduction zones such as those in the North Dabie UHP belts, China (e.g., Gao et al., 2017), the North Qinling orogen, China (e.g., Bader et al., 2020), and the Western Gneiss Region, Norway (e.g., Butler et al., 2018), it is reasonable to assume that the re‐equilibration of mineral compositions in the exhumation stage could lead to the calculated temperature ( T ) at P max to a higher value. In comparison to modeling results, temperatures recorded by exhumed oceanic rocks show smaller discrepancies than continental rocks (Agard et al., 2018; Penniston‐Dorland et al., 2015), supporting that part of the recovered peak P – T conditions of exhumed continental rocks with high temperatures may be influenced by decompressional heating.…”
Section: Introductionmentioning
confidence: 99%
“…In the East Qinling Orogen, the Qinling Complex is mainly comprised of amphibolite-facies to granulite-facies gneisses with subordinate amounts of UHP-HP and ultrahigh-temperature (UHT) rocks [14][15][16][17][18]. Most studies suggest that the UHP-HP rock in the East Qinling Orogen formed in 500-485 Ma, representing the Cambrian continental deep subduction, whereas the widely distributed amphibolite-facies to granulite-facies rocks with clockwise P-T paths formed in 450-400 Ma, reflecting the collision and post-collision (overprint) event [14][15][16][17][18][19][20][21][22]. However, some authors suggested the Silurian high-temperature metamorphic event in the East Qinling Orogen formed in arc or arc-related tectonic environments which were related to the subduction of the Shangdan Ocean [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%